Brazil's strategic partnerships: an assessment of the Lula era (2003-2010) - Lessa,Antônio Carlos (2010)
This article examines the priority bilateral relations of Brazil, named "strategic partnerships", both because of their tradition and historical relevance and due to the existence of political and economic cooperation projects. An assessment of these relationships, especially under Lula's administration, is made in this work, bearing in mind the concept of "strategic partnerships" and its development in Brazilian foreign policy. There will be considered partnerships with the US; Argentina; Japan; China; India; South Africa and the European Union. In the article, the meaning of the increase in these relationships is interpreted on the grounds of its significance to the international insertion strategy of Brazil